2008 IEEE International Conference on Computer Design 2008
DOI: 10.1109/iccd.2008.4751875
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of thread-level speculation in SMT and CMP architectures - performance, power and thermal perspective

Abstract: Abstract-Computer industry has adopted multi-threaded and multi-core architectures as the clock rate increase stalled in early 2000's. However, because of the lack of compilers and other related software technologies, most of the generalpurpose applications today still cannot take advantage of such architectures to improve their performance. Thread-level speculation (TLS) has been proposed as a way of using these multi-threaded architectures to parallelize general-purpose applications. Both simultaneous multit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Packirisamy et al [2008] compared and contrasted the energy efficiency of SMT and CMP in terms of supporting TLS workload under the same die area constraints. They examined how the interactions between speculative threads affect their energy efficiency in SMT-mode and CMP-mode execution.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Packirisamy et al [2008] compared and contrasted the energy efficiency of SMT and CMP in terms of supporting TLS workload under the same die area constraints. They examined how the interactions between speculative threads affect their energy efficiency in SMT-mode and CMP-mode execution.…”
Section: Related Workmentioning
confidence: 99%
“…Previous work has shown that SMT and CMP could result in different levels of energy efficiency [Packirisamy et al 2008]. Thus, we explore the possibility for both types of multithreading support.…”
Section: Introductionmentioning
confidence: 99%
“…Although EPIC processors are statically scheduled, they require extensive software/hardware assistance to provide the processor with information to deal with events such as branch prediction, load speculation, and necessary exception handling. As a result EPIC architectures require mechanisms to communicate this parallelism to its underlying hardware [45].…”
Section: Explicitly Parallel Instruction Processors (Epic)mentioning
confidence: 99%
“…[Packirisamy et al 2008;Tang et al 2005] compared SMT with CMP (Chip Multiprocessors) in the context of TLS, giving a perspective of performance, power and thermal;[Ungerer et al 2003] described chips that support multithreading. However, a full description of these processors is beyond the scope of this survey, and will not be provided.…”
mentioning
confidence: 99%